2021
DOI: 10.3389/fnbeh.2020.617418
|View full text |Cite
|
Sign up to set email alerts
|

Administration of N-acetylcysteine Plus Acetylsalicylic Acid Markedly Inhibits Nicotine Reinstatement Following Chronic Oral Nicotine Intake in Female Rats

Abstract: BackgroundNicotine is the major addictive component of cigarette smoke and the prime culprit of the failure to quit smoking. Common elements perpetuating the use of addictive drugs are (i) cues associated with the setting in which drug was used and (ii) relapse/reinstatement mediated by an increased glutamatergic tone (iii) associated with drug-induced neuroinflammation and oxidative stress.AimsThe present study assessed the effect of the coadministration of the antioxidant N-acetylcysteine (NAC) plus the anti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(10 citation statements)
references
References 92 publications
0
10
0
Order By: Relevance
“…NAC, however, restores resting‐state functional connectivity in this network, 51 and restoration of frontostriatal connectivity is associated with reduced craving and smoking relapse compared with placebo‐treated smokers 30 . Further, a recent study also found that NAC treatment normalized nicotine‐induced downregulation of GLT‐1 and glutamate cysteine exchanger expression in the prefrontal cortex of rats 52 . Thus, it appears that the combined VRN + NAC treatment approach proposed here confers effects in these separable circuits to reduce reinforcement and relapse of nicotine seeking.…”
Section: Resultsmentioning
confidence: 97%
See 1 more Smart Citation
“…NAC, however, restores resting‐state functional connectivity in this network, 51 and restoration of frontostriatal connectivity is associated with reduced craving and smoking relapse compared with placebo‐treated smokers 30 . Further, a recent study also found that NAC treatment normalized nicotine‐induced downregulation of GLT‐1 and glutamate cysteine exchanger expression in the prefrontal cortex of rats 52 . Thus, it appears that the combined VRN + NAC treatment approach proposed here confers effects in these separable circuits to reduce reinforcement and relapse of nicotine seeking.…”
Section: Resultsmentioning
confidence: 97%
“…30 Further, a recent study also found that NAC treatment normalized nicotine-induced downregulation of GLT-1 and glutamate cysteine exchanger expression in the prefrontal cortex of rats. 52 Thus, it appears that the combined VRN + NAC treatment approach proposed here confers effects in these separable circuits to reduce reinforcement and relapse of nicotine seeking.…”
Section: Translational Utility and Mechanismsmentioning
confidence: 88%
“…Chronic nicotine consumption causes oxidative stress, which inhibits astrocyte glutamate transporters ( Berríos-Cárcamo et al, 2020 ). Recent research suggests that cue-induced restoration of nicotine self-administration and chronic nicotine exposure in rats are linked with higher TNF-α levels in the PFC and NAc ( Namba, 2019 ; Quintanilla et al, 2021 ).…”
Section: Introductionmentioning
confidence: 99%
“…ASA works to reduce the synthesis of prostaglandin E2 and pro-inflammatory cytokines by inhibiting the cyclooxygenase COX-1 and COX-2 enzymes ( Israel et al, 2021 ). Importantly, ASA upregulates GLT-1 protein levels after chronic ethanol intake and chronic oral nicotine intake, blocks relapse to binge drinking, and inhibits nicotine reinstatement in female rats ( Quintanilla et al, 2020 ; Israel et al, 2021 ). ASA also increases GLT-1 levels in the PFC ( Quintanilla et al, 2021 ) and may also suppress the NF-κB pathway ( Dąbek et al, 2010 ).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation